Institutional Sustainability Analysis of Community-Based Tourism (Case of Kasbi Community in North Halmahera ) - Singgalen, Yerik Afrianto; Sasongko, Gatot; Wiloso, Pamerdi Giri (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
This study aims to analyze the sustainability of the implementation of the concept of community-based tourism especially in the Tourism Community in North Halmahera Regency known as